2007
DOI: 10.1007/s10162-007-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Behavioral Sensitivity to Interaural Time Differences Using Amplitude Modulated Tones with Mismatched Carrier Frequencies

Abstract: Bilateral cochlear implantation is intended to provide the advantages of binaural hearing, including sound localization and better speech recognition in noise. In most modern implants, temporal information is carried by the envelope of pulsatile stimulation, and thresholds to interaural time differences (ITDs) are generally high compared to those obtained in normal hearing observers. One factor thought to influence ITD sensitivity is the overlap of neural populations stimulated on each side. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…It has been reported that in postlingually deafened adults place (mis)matches may have an effect on the size of the electrical BMLD [Long et al, 2007], which means that possibly larger BMLDs would be obtained in these children with other electrode pairs. On the other hand, as shown in the literature, binaural sensitivity does not disappear with a shift in place of stimulation [Blanks et al, 2007;Long et al, 2003;van Hoesel, 2004]. Research with normal-hearing subjects has shown that envelope delays for carrier frequencies separated by up to 2 or 3 octaves can be perceived, a result that was confirmed by neural recordings in rabbits [Blanks et al, 2007].…”
Section: Bmlds In Children With Bilateral Cissupporting
confidence: 61%
See 1 more Smart Citation
“…It has been reported that in postlingually deafened adults place (mis)matches may have an effect on the size of the electrical BMLD [Long et al, 2007], which means that possibly larger BMLDs would be obtained in these children with other electrode pairs. On the other hand, as shown in the literature, binaural sensitivity does not disappear with a shift in place of stimulation [Blanks et al, 2007;Long et al, 2003;van Hoesel, 2004]. Research with normal-hearing subjects has shown that envelope delays for carrier frequencies separated by up to 2 or 3 octaves can be perceived, a result that was confirmed by neural recordings in rabbits [Blanks et al, 2007].…”
Section: Bmlds In Children With Bilateral Cissupporting
confidence: 61%
“…On the other hand, as shown in the literature, binaural sensitivity does not disappear with a shift in place of stimulation [Blanks et al, 2007;Long et al, 2003;van Hoesel, 2004]. Research with normal-hearing subjects has shown that envelope delays for carrier frequencies separated by up to 2 or 3 octaves can be perceived, a result that was confirmed by neural recordings in rabbits [Blanks et al, 2007]. A spacing of 10 mm on the basilar membrane corresponds to a frequency range of about 2.5 octaves [Greenwood, 1990] and to a range of 13 electrodes in the Nucleus CI.…”
Section: Bmlds In Children With Bilateral Cissupporting
confidence: 49%
“…Blanks et al (2007) however show that, for a simpler psychophysical task or an animal model, there is sensitivity to ITD when the interaural frequency difference increases up to several octaves.…”
Section: Introductionmentioning
confidence: 75%
“…In NH subjects, ITD thresholds as a function of mismatch have been measured using amplitude-modulated (AM) signals (Henning, 1974;Nuetzel and Hafter, 1981;Blanks et al, 2007;Blanks et al, 2008). The consistent trend in the results from these studies has been that with increasing mismatch, ITD JNDs increased.…”
Section: Introductionmentioning
confidence: 77%